PENGARUH INTERVAL PENCUPLIKAN DATA PASANG SURUT TERHADAP KONSTANTA HARMONIK PASANG SURUT (Studi Kasus Data Pasut Sadeng) - , MUHAMAD SAYDUL BILAD ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Tidal movement is a phenomenon of rise and fall of sea levels periodically caused by a combination of gravitation force and drag force of astronomical objects, especially by sun, earth and moon. Information on tidal characteristics can be obtained through tidal harmonic analysis that generates harmonic constituents. In general, tidal harmonic analysis uses sampling interval of 1 hour.However, it is does not rule out using tidal data sampled other then 1 hour. This research is intend to evaluate the effects of various sampling interval of tidal data on the respective of the harmonic constante. This research used tidal data from IOC (Intergoverment Oceanographic Comission) taken during the 369 days according to the results of sinodic period. This data was grouped into 7 groups based on different sampling interval namely 15 minutes, 30 minutes, 1 hour, 2 hours, 4 hours, 5 hours, 6 hours, and 12 hours. Harmonic constants were calculated is M2, S2, KI, O1, P1, K2, N2. Konstituent harmonics are use in analysis harmonic are main diurnal konstituent (O1, P1, K1) and semi-diurnal constituents (M2, S2, K2, N2) . There are spike and empty data from early evaluation of tidal data. Spike and empty data were replaced using interpolated data from cubic spline interpolation. Aliasing principle should be applied to the harmonic components with frequencies outside the range of the nyquist frequency before tidal harmonic analysis performed. Harmonic analysis was performed on each group of data using tidal harmonic analysis program code by the oceanography team Institute Technology of Bandung. The results of tidal harmonic analysis was then analyzed to determine the quality of the harmonic constituents. Analysis was conducted on the significance analisis of differences in the value of the amplitude and phase difference for each group of data to the data with a sampling interval of 1 hour. Tidal harmonic analysis with a sampling interval of 15 minutes, 30 minutes, 1 hour, 2 hours, 4 hours, and 5 hours producesconsistent amplitude values, while the values of phase difference indicate rhythmic difference and specific values to each component refers to the sampling interval 1 hour. Sampling interval of 6 hours and 12 hours resulted in the value of the amplitude and the phase difference isinconsistent even extreme.This is due to the phenomenon of aliasing and commonality of components with periods of sampling interval. If desired to use interval data sampling other than 1 hour but less than 6, it is recommended to use the data sampling interval for 5 hours, because this data still produce a consistent amplitude, however phase different should be correct using incrementally ritmik value refer to 1 hour of sampling interval,with notes already exists data sampling interval 1 hour that used to determine the rhythmic phase difference.